2003
DOI: 10.1038/sj.leu.2402880
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of quantitative real-time RT-PCR parameters for the study of lymphoid malignancies

Abstract: Real-time quantitative reverse transcription polymerase chain reaction (RT-PCR) is a powerful method for measurement of gene expression for diagnostic and prognostic studies of nonHodgkin's lymphomas (NHL). In order for this technique to gain wide applicability, it is critically important to establish a uniform method for normalization of RNA input. In this study, we have determined the best method to quantify the RNA/cDNA input per reaction and searched for the most useful endogenous control genes for normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 23 publications
2
114
0
3
Order By: Relevance
“…There are no housekeeping genes whose expression is constant in all tissues during normal or malignant growth [19,20] . To properly control for the variation in expression of RNAs, endogenous control genes need to be used for each cell type and tumor type in each experimental design [21] . Here, we chose four housekeeping genes with different abundances that have been widely cited in the literature, and exhibit relatively low variation in expression in different lymphoid tissues [9,21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no housekeeping genes whose expression is constant in all tissues during normal or malignant growth [19,20] . To properly control for the variation in expression of RNAs, endogenous control genes need to be used for each cell type and tumor type in each experimental design [21] . Here, we chose four housekeeping genes with different abundances that have been widely cited in the literature, and exhibit relatively low variation in expression in different lymphoid tissues [9,21] .…”
Section: Discussionmentioning
confidence: 99%
“…To properly control for the variation in expression of RNAs, endogenous control genes need to be used for each cell type and tumor type in each experimental design [21] . Here, we chose four housekeeping genes with different abundances that have been widely cited in the literature, and exhibit relatively low variation in expression in different lymphoid tissues [9,21] . Our experiments indicated that the GUSB gene exhibited the lowest variation of expression in formalin-fixed, paraffinembedded and frozen lung cancer specimens, and should be used as a suitable endogenous gene to control for RNA quality and quantity.…”
Section: Discussionmentioning
confidence: 99%
“…We have also analyzed AID expression in DLBCL expression data reported by Rosenwald et al 20 In addition, AID mRNA expression in Burkitt lymphoma cell lines (Raji and Daudi), GCB-like DLBCL cell lines (SUDHL4, SUDHL6, OCILY7, OCILY19) and ABC-like DLBCL (OCILY10 and OCILY3) cultured with and without 100 U/ml IL-4 (R&D Systems, Minneapolis, MN, USA) was measured by real-time PCR using the Applied Biosystems Assays-on-Demandt Gene Expression Product on an ABI PRISM s 7900HT Sequence Detection System (Applied Biosystems, Foster City, CA, USA) and was normalized to the 18S expression that was used as an endogenous RNA/cDNA quantity control as we reported previously. 21 …”
Section: Tissue Specimens and Aid Expressionmentioning
confidence: 99%
“…PRAME expression was quantified using the TaqMan system, and intensity was calculated relative to that of PRKG1 gene expression (37). The positive control K562 cell line demonstrated the highest level of relative PRAME expression, 2.1.…”
Section: Prame Expression By Real Time Quantitative Taqman Pcr In Hclmentioning
confidence: 99%